Overcoming Access Barriers for Veterans: Cohort Study of the Distribution and Use of Veterans Affairs' Video-Enabled Tablets Before and During the COVID-19 Pandemic - Zainub Dhanani; Jacqueline M Ferguson; James Van Campen; Cindie Slightam; Josephine C Jacobs; Leonie Heyworth; Donna Zulman (JMIR Publications, 2023)
BackgroundDuring the COVID-19 pandemic, as health care services shifted to video- and phone-based modalities for patient and provider safety, the Veterans Affairs (VA) Office of Connected Care widely expanded its video-enabled tablet program to bridge digital divides for veterans with limited video care access. ObjectiveThis study aimed to characterize veterans who received and used US Department of VA-issued video-enabled tablets before versus during the COVID-19 pandemic. MethodsWe compared sociodemographic and clinical characteristics of veterans who received VA-issued tablets during 6-month prepandemic and pandemic periods (ie, from March 11, 2019, to September 10, 2019, and from March 11, 2020, to September 10, 2020). Then, we examined characteristics associated with video visit use for primary and mental health care within 6 months after tablet shipment, stratifying models by timing of tablet receipt. ResultsThere was a nearly 6-fold increase in the number of veterans who received tablets in the pandemic versus prepandemic study periods (n=36,107 vs n=6784, respectively). Compared to the prepandemic period, tablet recipients during the pandemic were more likely to be older (mean age 64 vs 59 years), urban-dwelling (24,504/36,107, 67.9% vs 3766/6784, 55.5%), and have a history of housing instability (8633/36,107, 23.9% vs 1022/6784, 15.1%). Pandemic recipients were more likely to use video care (21,090/36,107, 58.4% vs 2995/6784, 44.2%) and did so more frequently (5.6 vs 2.3 average encounters) within 6 months of tablet receipt. In adjusted models, pandemic and prepandemic video care users were significantly more likely to be younger, stably housed, and have a mental health condition than nonusers. ConclusionsAlthough the COVID-19 pandemic led to increased distribution of VA-issued tablets to veterans with complex clinical and social needs, tablet recipients who were older or unstably housed remained less likely to have a video visit. The VA's tablet distribution program expanded access to video-enabled devices, but interventions are needed to bridge disparities in video visit use among device recipients.